Exploring the genetic alterations of Gorham-Stout disease - Pagliarosi, Olivia; Pepe, Jessica; Del Fattore, Andrea; Rossi, Michela (Frontiers in Endocrinology, 2025)
The “vanishing bone disease” or Gorham-Stout disease (GSD) is a very rare disorder characterized by massive lymphatic and angiomatous proliferation accompanied by progressive osteolysis, without the deposition of new bone matrix. Because of its rare and complex clinical features, diagnosis is challenging and its etiopathogenesis is not completely known; the genetic basis of GSD has been hypothesized and different mutations have been reported in patients. Our review aims to describe all these genetic alterations found in GSD patients and their association with clinical features. The identification of a specific molecular pathway or genetic alteration in GSD could help in the diagnosis and possibly the treatment of this rare sporadic disease.